Extended Medial Gastrocnemius Myocutaneous Flap (A Case Report) - Saha, Ila; Sinha, P.; Banerjee, A. K. (Indian Journal of Plastic Surgery, 1987)
The extended gastrocnemius myocutaneous flap is a good technique for reconstruction of skin and soft tissue loss of the lower third leg defects. We have obtained satisfactory result in our case by using this flap.